Analisis Proses Kerja Administrasi Menggunakan Aplikasi DALANG Pada Pusat Pengelolaan Komplek Gelora Bung Karno (PPKGBK) - Endah Sahira; Roni Faslah; Ferry Setyadi Atmadja (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the administrative work process through the DALANG Application (Online Budget Control) at the Gelora Bung Karno Complex Management Center (PPKGBK), identify operational constraints, and formulate improvement recommendations. This research employed a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and document review involving four purposively selected informants. Data analysis was conducted using Sugiyono’s (2019) interactive analysis model, while data validity was ensured through technical triangulation. The findings reveal that the implementation of the DALANG Application remains in a transition phase toward full digitalization, characterized by a semi-digital workflow involving parallel physical and digital processes. The main operational challenges include dependence on manual documents, the requirement for wet signatures, and centralized journal correction processes at the Central Cash Division, which contribute to delays in reporting. These findings indicate that digitalization has not yet fully optimized administrative effectiveness. Therefore, improvements are required through stronger system integration, digital feature optimization, and administrative procedure simplification to support more effective digital transformation.